6x-7y+3a=

Simple and best practice solution for 6x-7y+3a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-7y+3a= equation:


Simplifying
6x + -7y + 3a = 0

Reorder the terms:
3a + 6x + -7y = 0

Solving
3a + 6x + -7y = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6x' to each side of the equation.
3a + 6x + -6x + -7y = 0 + -6x

Combine like terms: 6x + -6x = 0
3a + 0 + -7y = 0 + -6x
3a + -7y = 0 + -6x
Remove the zero:
3a + -7y = -6x

Add '7y' to each side of the equation.
3a + -7y + 7y = -6x + 7y

Combine like terms: -7y + 7y = 0
3a + 0 = -6x + 7y
3a = -6x + 7y

Divide each side by '3'.
a = -2x + 2.333333333y

Simplifying
a = -2x + 2.333333333y

See similar equations:

| 4x+b=a | | 8+4x=-20 | | -3c+60=18c-108 | | x^2+11x=80 | | 299.32=C+84.34 | | (y^2+8)(y^2-8)= | | 100=5w | | (y-8)(y-8)= | | (x+2)(x-1)=x^2+5 | | 3c+60=18c-108 | | 33-2x=7x+23 | | m=-6-(-10) | | -5x-15=2x+12 | | m=10-(-6) | | (x-1)(x+2)=x^2+5 | | 4-21= | | 56-26= | | 56-21= | | 6x-25=3x+50 | | 78/6 | | -1+x=2(2x-8) | | 15x+15y=30 | | x+3=2(2x-3) | | 1.7C-1.4=7.1 | | m/6=m+7/10 | | 9=p-s | | 5-2x=5-4x | | 20v=u | | 18P+21-9P=21 | | (x+4)*x=262 | | n=m+12 | | -5(x+6)-43=8-36 |

Equations solver categories